Smart assistant for visually impaired navigation on tactile paving using ESP32 - Mohd Hadzir, Amirul Asyraf; Kamarulzaman, Khairul Haqimie; Mohamad Nasir, Zaril Luqman; Teh Yen Li, Jerelyn; Baharuddin, Nur Amirah Syahirah; Halim, Zulkifli (2025)
The main challenge of visually impaired individuals is the movement from one destination to another, especially in urban environment through the public walkways. Even though the local authority has provided the tactile paving facility as the basic guidance for them, it is still lacking the capability to detect nearby obstacles and alert to the blind people. This project aims to propose a smart assistive device for visually impaired individuals to get through tactile paving walkways using ESP32 microcontroller and integrated with proximity sensors. The proof-of-concept (POC) make use the ultrasonic and infrared (IR) distance sensors to detect close obstacles. The system will be alarming to the blind people via a buzzer or speaker when the sensors detected. The suggested prototype, like wearable or handheld, will demonstrate real-time feedback that increases safety for the blinds. Light Detection and Ranging (LiDAR) is proposed to be integrated for the real-world readiness device to improve spatial accuracy. This POC serves to validate the feasibility of a low-cost, sensor-driven mobility assistant. This project has the potential to improve the quality of life for visually impaired individuals in urban environments.